Comparative analysis of in vitro oxidative degradation of poly(carbonate urethanes) for biostability screening. Issue 10 (21st November 2013) - Dempsey, David K.; Carranza, Christopher; Chawla, Chander P.; Gray, Patrick; Eoh, Joon H.; Cereceres, Stacy; Cosgriff‐Hernandez, Elizabeth M.
Abstract The resistance to oxidation and environmental stress cracking of poly(carbonate urethanes) (PCUs) has generated significant interest as potential replacements of poly(ether urethanes) in medical devices. Several in vitro models have been developed to screen segmented polyurethanes for oxidative stability. High concentrations of reactive oxygen intermediates produced by combining hydrogen peroxide and dissolved cobalt ions has frequently been used to predict long‐term oxidative degradation with short‐term testing. Alternatively, a 3% H2O2 concentration without metal ions is suggested within the ISO 10993‐13 standard to simulate physiological degradation rates. A comparative analysis which evaluates the predictive capabilities of each test method has yet to be completed. To this end, we have utilized both systems to test three commercially available PCUs with low and high soft segment content: Bionate® PCU and Bionate® II PCUs, two materials with different soft segment chemistries, and CarboSil® TSPCU, a thermoplastic silicone PCU. Bulk properties of all PCUs were retained with minor changes in molecular weight and tensile properties indicating surface oxidative degradation in the accelerated system after 36 days. Soft segment loss and surface damage were comparable to previous in vivo data. The 3% H2O2 method exhibited virtually no changes on the surface or in bulk properties after 12 months of treatment despite previous in vivo results. These results indicate the accelerated test method more effectively characterized the oxidative degradation profiles than the 3% H2O2 treatment system. The lack of bulk degradation in the 12‐month study also supports the hydrolytic stability of these PCUs. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 3649–3665, 2014.